"Orandum est ut sit mens sana in corpore sano", or the Beginnings of health Prevention in Antiquity - Judyta Krajewska (The Francis de Sales Scientific Society (TNFS.PL), 2022)
The article makes an attempt at providing answers to questions necessary to clarify the doubts related to the universal conviction about the breakthrough of the nineteenth century for the development of health promotion and health prophylaxis. Can ancient texts provide any evidence that it was actually the antiquity that laid the foundations for preventive medicine? Can it be concluded, on the basis of the research conducted by archaeologists, anthropologists and historians, that the increased physical activity and use of diet in antiquity were deliberate preventive actions?